Expression Profile of VEGF-C, VEGF-D, and VEGFR-3 in Different Grades of Endometrial Cancer - Oplawski, Marcin; Dziobek, Konrad; Zmarzły, Nikola; Grabarek, Beniamin; Halski, Tomasz; Januszyk, Piotr; Kuś-Kierach, Agnieszka; Adwent, Iwona; Dąbruś, Dariusz; Kiełbasiński, Kamil; Boroń, Dariusz (Current Pharmaceutical Biotechnology, 2019)
Background: Vascular endothelial growth factor (VEGF)-C, -D, and VEGF receptor-3 are proteins characterized as crucial for tumor lymphangiogenesis. It is accompanied by angiogenesis during wound healing, but also in the neoplastic process. The research studies have shown that the lymphatic system plays a key role in the progression of carcinogenesis. Objective: The aim of this study was to evaluate changes in the expression of VEGF-C, VEGF-D and VEGFR-3 in different grades of endometrial cancer (G1-G3). Methods: The study included 45 patients diagnosed with endometrial cancer (G1=17; G2=15; G3=13) and 15 patients without neoplastic changes. The expression of VEGF-C, VEGF-D, and VEGFR-3 was assessed using microarray technique and immunohistochemistry. Statistical analysis was performed using the one-way ANOVA and Tukey's post-hoc test. Results: Statistically significant changes in the expression at the transcriptome level were found only in the case of VEGF-C (G1 vs. C, fold change - FC = -1.15; G2 vs. C, FC = -2.33; G3 vs. C, FC = - 1.68). However, VEGF-D and VEGFR-3 were expressed at the protein level. Analysis of VEGF-D expression showed that the optical density of the reaction product in G1 reached 101.7, while the values in G2 and G3 were 142.7 and 184.4, respectively. For VEGF-R3, the optical density of the reaction product reached the following levels: 72 in control, 118.77 in G1, 145.8 in G2, and 170.9 in G3. Conclusion: An increase in VEGF-D and VEGFR-3 levels may indicate that VEGF-D-dependent processes are intensified along with the dedifferentiation of tumor cells. The lack of VEGF-C expression in endometrial cancer samples may suggest that this tumor is characterized by a different mechanism of metastasis than EMT. Our study emphasizes that when analyzing the metastatic potential of cancer, the expression of more than one factor should be taken into account.
Keywords: VEGFR-3